GAMBARAN BOUNDING ATTACHMENT PADA IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS ANDONGSARI KABUPATEN JEMBER - Amalia, Firriana Rizqi; Kurniawati, Dini; Sulistyorini, Lantin (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2024)
Abstract: The formation of bounding attachment was the formation of a bond of affection between mother and child which might be formed from birth. One of the formations of bounding attachment was through exclusive breastfeeding. However, the purpose and method of this study was to describe the bounding attachment of breastfeeding mothers in the working area of Andongsari Public Health Center, through a retrospective approach with an analytic descriptive design used a purposive sampling method. Thus, this study involved 61 respondents who were breastfeeding mothers. The research results obtained were breastfeeding mothers in the Andongsari Health Center work area showing good bounding attachments with a total of 57 respondents (93.4%) and as many as 4 respondents (6.6%) showing unfavorable bounding attachments. The conclusion of this study was that the description of bounding attachment to breastfeeding mothers in the Andongsari Health Center work area showed good results with good information from posyandu administration, sharing information with other mothers regarding child care and care. The implications that could be applied to this research were health promotion related to the upbringing and care of children, facilitating counseling related to child planning, supporting mothers in the lactation process, and increasing interaction between babies and mothers.Abstrak: Pembentukan bounding attachment merupakan pembentukan ikatan kasih sayang antara ibu dan anak yang harus di bentuk sejak lahir. Salah satu pembentukan bounding attachment yaitu dengan melalui pemberian ASI eksklusif. Tujuan dan metode penelitian ini adalah untuk mengetahui gambaran bounding attachment pada ibu menyusui di wilayah kerja Puskesmas Andongsari, melalui pendekatan retrospektif menggunakan desain deskriptif analitik dengan metode purposive sampling. Penelitian ini melibatkan 61 responden ibu menyusui. Hasil penelitian yang diperoleh yaitu pada ibu menyusui di wilayah kerja Puskesmas Andongsari menunjukkan bounding attachment yang baik dengan jumlah 57 responden (93,4 %) dan sebanyak 4 responden (6,6 %) menunjukkan bounding attachment yang kurang baik. Kesimpulan dari penelitian ini yaitu gambaran bounding attachment pada ibu menyusui di wilayah kerja Puskesmas Andongsari menunjukkan hasil yang baik. Implikasi yang bisa diterapkan dengan adanya penelitian ini yaitu promosi kesehatan terkait dengan pengasuhan dan perawatan anak, memfasilitasi konseling terkait dengan perencanaan anak, mendukung ibu dalam proses laktasi, meningkatkan interaksi antara bayi dan ibunya.